CONCEPTUALIZATION AND GENEALOGY : A LOVE BASED CURRICULUM GROUNDED IN GENDER EQUALITY IN PRIMARY MADRASAH TEACHER EDUCATION - bella, sinta; Halimatus Sya’diyah; , Siti Asiya; Maimun (PGMI UNHASY, 2026)
Madrasah Teacher Education (PGMI) plays a strategic role in shaping the pedagogical competence, personal character, and social sensitivity of prospective teachers who will directly engage with elementary-level students. However, teacher education curricula still tend to emphasize methodological and cognitive aspects, while affective dimensions Primary and gender awareness have not been systematically integrated. This article aims to examine, first, the conceptualization of a love-based curriculum grounded in gender equality within the context of Primary Madrasah Teacher Education. Second, it explores the genealogy of the idea of a love-based curriculum rooted in gender equality. This study employs a qualitative approach using a library research design. Research data were obtained through a review of literature, including books, scholarly journal articles, and relevant educational policy documents. Data collection was conducted through documentation study, while data analysis utilized conceptual analysis and historical (genealogical) analysis through stages of data reduction, concept categorization, critical interpretation, and conclusion drawing. The findings indicate that a love-based curriculum grounded in gender equality in MI teacher education is understood as a pedagogical framework that emphasizes compassion, empathy, justice, and respect for gender differences as the foundation for shaping teachers’ habitus. The genealogy of this idea can be traced from religious teachings on rahmah (compassion), humanistic thought, Paulo Freire’s critical pedagogy, to contemporary feminism, which positions love as a practice of liberation. This article contributes to the discourse on teacher education by emphasizing the importance of integrating affective pedagogy and gender awareness into the PGMI curriculum.